Effectiveness of treatment based on parent-child interaction with virtual education method on the executive functions of students with hyperactivity and attention deficit disorder - Bayat, Sahar; Shahriari Ahmadi, Mansoureh; Estaki, Mahnaz (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and purpose: People with attention deficit hyperactivity disorder are characterized by hyperactivity, impulsivity and inattention. The present study was conducted with the aim of the effectiveness of parent-child interaction therapy with virtual education method on the executive functions of students with hyperactivity and attention deficit disorder. Methods: The research method was quasi-experimental, with a pre-test and post-test design with a control group. The statistical population of the study was all children aged 10 to 12 years in the 19th district of Tehran in 2021 who were suffering from hyperactivity and attention deficit. The sample size of 30 people was determined by the purposeful sampling method, this number of people was divided into two groups by the matching method, the number of each group was 15 people, and an experimental group received treatment based on parent-child interaction through virtual training. And the control group did not receive any treatment program. The research tool was the executive functions questionnaire of Gerard et al. (2000). The method of data analysis was univariate and multivariate covariance analysis and Spss.22 software. Results: The findings of the research showed that the treatment based on parent-child interaction with the virtual education method is effective on the executive functions of students with hyperactivity and attention deficit (p<0.05). Conclusion: It can be concluded that the treatment based on parent-child interaction with the virtual education method can be effective in improving the executive functions of students with hyperactivity and attention deficit disorder.